Differences in perception of stress of physiotherapists employed in various departments - Milojević, Mia (Array, 2020)
Stress in the workplace represents a specific type of stress, stemming from the work environment. Stressful situations at work can trigger negative emotions that are linked with anxiety, tension, depression, fatigue and lack of working motivation. The aim of this research is to investigate differences in the perception of stress of physiotherapists employed in various departments. The research was conducted using an online questionnaire aimed at 123 physiotherapists in the Republic of Croatia. The results have showed that respondents perceived their workplace as moderately stressful. Considering the difference in the experience and perception of stress with regard to the department where physiotherapists work, the results have showed that there is a statistically significant difference in the level of perceived stress among the respondents with regard to the department in which they are employed. It was found that respondents employed in orthopaedics perceived stress to a lesser extent than those individuals employed in health centres and in the department of physical medicine and rehabilitation. The differences in the perception of stress among the respondents who are employed in other departments have shown no statistically significant difference. It was shown that the respondents of 20–25 years of age were found to exhibit statistically significantly lower levels of perceived stress compared to subjects of 26–36 years of age. There is no noted statistically significant difference in the perception of stress among other age groups. It was determined that participants with a lower net monthly salary exhibit statistically significant greater lever of perceived stress in comparison to participants with a net monthly salary that is greater than the average.